Synthesis and Characterization of Aero-Eutectic Graphite Obtained by Solidification and Its Application in Energy Storage: Cathodes for Lithium Oxygen Batteries - Gregorutti, Ricardo Walter (2020)
Aero-eutectic graphite can be defined as a new light material with hierarchically structured porosity. It is obtained from the solidification of gray cast irons, followed by the dissolution of the ferrous matrix by an acidic sequence. The result is a continuous and interconnected network of graphite sheets with varied dimensions randomly oriented. X-ray diffraction characterization has revealed graphite crystallographic planes (002), (100), (101), (102) and (004), while the surface area measured by BET and Langmuir methods has been determined in the order of 90 m2 g−1 and 336 m2 g−1, respectively. The process of obtaining eutectic aero-graphite also allows the deposit of Cu nanofilms and TiC particles. Aero-eutectic graphite has been tested as cathode in Li?O2 batteries as it has been prepared, without the addition of binders or conductive carbons, showing an appropriate contact with the electrolyte, so that the oxygen reduction and evolution reactions may develop satisfactorily. In the discharge-charge galvanostatic tests, the battery accomplishes 20 complete cycles with area capacity limited to 1.2 mAh cm−2.